2013
DOI: 10.1371/journal.pone.0055514
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Running Wheel for Detection of Congestive Heart Failure in Dilated Cardiomyopathy Mouse Model

Abstract: BackgroundInherited dilated cardiomyopathy (DCM) is a progressive disease that often results in death from congestive heart failure (CHF) or sudden cardiac death (SCD). Mouse models with human DCM mutation are useful to investigate the developmental mechanisms of CHF and SCD, but knowledge of the severity of CHF in live mice is necessary. We aimed to diagnose CHF in live DCM model mice by measuring voluntary exercise using a running wheel and to determine causes of death in these mice.Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
14
0
2
Order By: Relevance
“…Thus far, only a few studies have revealed the effects of ARBs on DCM using animal models [23], and these studies have not assessed the effects of ARBs on electrical remodeling in inherited DCM. In the present study, we found that candesartan improved the survival rate and cardiac systolic function, and suppressed progression of cardiac dilation and fibrosis using a DCM mouse model with the ΔK210 mutation in TNNT2 , which closely recapitulates the human phenotype [12][14], [16]. In addition to the above effects, candesartan suppressed occurrence of ventricular arrhythmia as well as various changes in the electrical properties in DCM hearts.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Thus far, only a few studies have revealed the effects of ARBs on DCM using animal models [23], and these studies have not assessed the effects of ARBs on electrical remodeling in inherited DCM. In the present study, we found that candesartan improved the survival rate and cardiac systolic function, and suppressed progression of cardiac dilation and fibrosis using a DCM mouse model with the ΔK210 mutation in TNNT2 , which closely recapitulates the human phenotype [12][14], [16]. In addition to the above effects, candesartan suppressed occurrence of ventricular arrhythmia as well as various changes in the electrical properties in DCM hearts.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, treatment of DCM mice with candesartan was started at 1 month of age when their death rate was still low [13] , [16] . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the homozygous D73N (+/+) mice survived longer than one day. The phenotype of the D73N (+/−) mice resembled that of homozygous knock-in mice harboring the DCM-linked ΔK210 mutation in cTnT (homozygous ΔK210cTnT mice) (Du et al, 2007 ; Sugihara et al, 2013 ). Like the D73N (+/−) mice, homozygous ΔK210cTnT mice developed early onset DCM, with decreased Ca 2+ sensitivity of force development, enlarged hearts, left ventricular dilation, and systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Some indicators of HF, such as atrial natriuretic peptide and brain natriuretic peptide, have been found to be more closely correlated with cardiac enlargement than CHF or lung edema (Sugihara et al, 2013;Lourenco et al, 2010). CRP levels are elevated in CHF and increasing levels are associated with increasing morbidity and mortality in ischemic and non-ischemic etiologies (Nakagomi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%